Optimalisasi Efektivitas Whistleblower dalam Pengungkapan Tindak Pidana Korupsi Dalam Pandangan Perspektif Hukum - Asri Puannandini, Dewi; Alrifkie; Sivanni, Najwa; Nuraeni, Risti Dea; Ristiani (Universitas Medan Area, 2025)
The purpose of this study is to determine the effectiveness of the role of whistleblowers in exposing corruption crimes in Indonesia and to determine the extent to which protection and the legal system can protect whistleblowers and encourage whistleblower courage. This research uses a normative juridical method with a statutory approach to analyze laws and regulations related to corruption crimes. The results show that the whistleblower system plays an important role in efforts to eradicate corruption, but its implementation still faces significant challenges. Data reveals that 90% of whistleblowers lose their jobs after reporting, although 84% are still willing to report again. A Transparency International Indonesia survey showed 68% of respondents were ready to become whistleblowers. The effectiveness of the system is influenced by five factors: legal framework, law enforcement, facilities, public awareness, and culture. Despite a 25% increase in the LPSK budget by 2023, legal protection is still not optimal. The research recommends strengthening regulations, improving the protection system, intensifying public education, strengthening organizational culture, and developing an incentive system to increase the effectiveness of the whistleblowing system in combating corruption in Indonesia.